Analysis of the Influence of Organizational Behavior on the Effectiveness of Digital Marketing Strategies in Improving Competitiveness at Nine Café & Resto, Soppeng Regency - Asmini Asmini; Nur Aulia; Puji Rahmah; Wildayanti Wildayanti (GENTARA: management and accounting research, 2026)
This study aims to analyze the impact of organizational behavior on the effectiveness of digital marketing strategies in enhancing competitiveness at Nine Cafe & Resto in Soppeng Regency. In today’s competitive business environment, digital marketing has become a critical tool for improving customer engagement and increasing market visibility. However, the success of digital marketing strategies depends not only on the technology used but also on the organizational culture that supports its implementation. The research employs a mixed-method approach, combining qualitative interviews with management and staff to understand organizational behavior and leadership, along with quantitative surveys distributed to customers to assess the effectiveness of digital marketing. The results indicate that a supportive organizational culture, proactive leadership, and active employee involvement significantly enhance the effectiveness of digital marketing strategies. The study concludes that organizational behavior plays a crucial role in the success of digital marketing, which directly contributes to improving the competitive advantage of Nine Cafe & Resto